2005
DOI: 10.1152/japplphysiol.00613.2005
|View full text |Cite
|
Sign up to set email alerts
|

Ovalbumin sensitization alters the ventilatory responses to chemical challenges in guinea pigs

Abstract: tients with chronic bronchial asthma show a depressed ventilatory response to hypoxia (DVH), but the underlying mechanism remains unclear. We tested whether DVH existed in ovalbumin (Ova)-treated guinea pigs, an established animal model of asthma. Twelve guinea pigs were exposed to Ova (1% in saline) or saline aerosol (control) for 5 min, 5 days/wk, for 2 wk. After completing aerosol exposure, the animals were anesthetized and exposed to systemic hypoxia. Ova treatment had no effects on animal body weight, bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 39 publications
2
1
0
Order By: Relevance
“…3-5). Recent investigations reported that OVA sensitization significantly enhanced PCF activities (6) and the apneic response to capsaicin (57). The results of the present study also provide the direct electrophysiological evidence demonstrating the OVA sensitization induced PCF hypersensitivity.…”
Section: Discussionsupporting
confidence: 80%
“…3-5). Recent investigations reported that OVA sensitization significantly enhanced PCF activities (6) and the apneic response to capsaicin (57). The results of the present study also provide the direct electrophysiological evidence demonstrating the OVA sensitization induced PCF hypersensitivity.…”
Section: Discussionsupporting
confidence: 80%
“…We found that the latency to evoke the initial apnea was ϳ1.7 s in weanling and adult rats, similar to that previously reported in postnatal and adult anesthetized rats and cats (20,33,34,36,37). Interestingly, in the present study, RSV infection prolonged the initial apneic duration by 40%, which is much smaller than the CAP impacts on the following apneas (the longest apneic duration was prolonged by 650% and the apneic episodes by 139%).…”
Section: Discussionsupporting
confidence: 91%
“…When the antigen OVA was injected into pre-sensitized, isolated guinea pig hearts, immediate and dramatic cardiac functional changes occurred [18]. Namely, the coronary flow diminished markedly and the contractile force increased initially (in about 2 min post-OVA challenge in this…”
Section: Discussionmentioning
confidence: 99%